Comparative study of concatemer efficiency as an isotope-labelled internal standard for allergen quantification. (1st December 2020) - Gavage, Maxime; Van Vlierberghe, Kaatje; Van Poucke, Christof; De Loose, Marc; Gevaert, Kris; Dieu, Marc; Renard, Patsy; Arnould, Thierry; Filee, Patrice; Gillard, Nathalie
Highlights: Multiple food allergens quantification by mass spectrometry. Stable isotope-labelled concatemer internal standard. Concatemer, synthetic peptide and protein comparison as internal standards. Abstract: Mass spectrometry-based methods coupled with stable isotope dilution have become effective and widely used methods for the detection and quantification of food allergens. Current methods target signature peptides resulting from proteolytic digestion of proteins of the allergenic ingredient. The choice of appropriate stable isotope-labelled internal standard is crucial, given the diversity of encountered food matrices which can affect sample preparation and analysis. We propose the use of concatemer, an artificial and stable isotope-labelled protein composed of several concatenated signature peptides as internal standard. With a comparative analysis of three matrices contaminated with four allergens (egg, milk, peanut, and hazelnut), the concatemer approach was found to offer advantages associated with the use of labelled proteins, ideal but unaffordable, and circumvent certain limitations of traditionally used synthetic peptides as internal standards. Although used in the proteomic field for more than a decade, concatemer strategy has not yet been applied for food analysis.